PENERAPAN CONFIGURAL FREQUENCY ANALYSIS (CFA) UNTUK MENENTUKAN KARAKTERISTIK USER DAN NON USER MOTOR X DI KOTA CIREBON (Studi Kasus PT. XYZ) - Muhamad Iqbal Mawardi; Bertho Tantular; Resa Septiani Pontoh (Universitas Jenderal Soedirman, 2017)
ABSTRACT. PT. XYZ has a role as the main dealer of motor X in West Java with marketing area in three cities: Bandung, Bekasi and Cirebon. The company survey always held every year about Brand Awareness & Image to users and non user motor X to know the characteristics of consumers. Based on the company report survey there was a decrease in the indicators of Top Of Mind Unit in Cirebon City for the user of 30.8% and for non users of 9.8%. This study aims to determine the characteristics that cause the decline of the Top Of Mind Unit based on the configuration of user characteristics and non user motor X in Cirebon City by using Configural Frequency Analysis (CFA). From the results of data analysis can be seen that there are three configurations of user characteristics and non users that deviate from the base model is formed. These three configurations can be considered in determining the marketing strategy to maintain and improve the Top Of Mind Unit in Cirebon City.